THE INFLUENCE OF DIALOGUE JOURNAL WRITING IN REDUCING EFL STUDENTS’ WRITING ANXIETY - Yuseva Ariyani Iswandari (Universitas Katolik Indonesia Atma Jaya, 2013)
Writing is considered important because it is one of the fourEnglish skills that take a significant role in the success of students’language learning. However, it is undeniable that writing, especiallyfor EFL college students, is still regarded difficult and frustrating(Graham, Harris, & Mason, 2005). As a result, students experiencewriting anxiety which affects the quality of their writing. This paperinvestigated factors that influenced students’ writing anxiety andhow dialogue journal writing helped students reduce their writinganxiety. This study was based on qualitative research in whichanxiety rubric from Ferris & Hedgcock (1998) and questionnaireswere administered to gather the data. Besides, samples of journalentries were also used as data collections. The study concluded thatthere were three major factors influencing the students’ writinganxiety: (1) making grammatical mistakes, (2) having difficulty infinding ideas, and (3) making minimum requirement mistakes. Thestudy also revealed 5 specific ways on how dialogue journal helpedthe students reduce their writing anxiety: (1) Learninggrammatically correct sentences, (2) creating a writing habit, (3)providing good examples on how to develop ideas, (4) Learningminimum requirement, and (5) facilitating student-teacher relation.Keywords: EFL students’ writing anxiety dialogue journalwriting